Pengaruh Return on Assets, Return on Equity, Earning Per Share dan Debtto Equity Ratio Terhadap Harga Saham - Kadek Angga Tirta; Partiwi Dwi Astuti; Ni Nyoman Sri Rahayu Damayanti (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2022)
This research aims to analyze the effect of return on assets, return on equity, earnings per share, and debt to equity ratio on stock prices. The population of this study is a consumer goods industry sector company listed on the Indonesia Stock Exchange for the period 2017-2019. The determination of the sample was done using purposive sampling techniques and there were 23 companies that were research samples from 40 companies during the pangamatan period. The data used in this study is secondary data in the form of company financial statements with the year 2017, 2018, 2019 obtained from the www.idx.co.id website. Data analysis techniques use descriptive statistics, classical assumption tests, and multiple linear regressions. The results of this study show that return on asset negatively and significantly affects stock prices; return on equity has a positive and significant effect on the stock price; earnings per share have a positive and significant effect on the stock price; and the debt to equity ratio has a negative and insignificant effect on the stock price.